Update on fixation of rigid and foldable posterior chamber intraocular lenses, part I: elimination of fixation-induced decentration to achieve precise optical correction and visual rehabilitation - Ram, Jagat; Apple, David J.; Peng, Qun; Visessook, Nithi; Auffarth, Gerd U.; Schoderbek, Robert J.; Ready, Edgar L. (Ophthalmology, 2003)
Purpose - Realizing that precise posterior chamber intraocular lens (PC-IOL) centration is needed to consistently achieve good optical results and visual rehabilitation after modern cataract surgery, the authors assessed the status and success rate of lens haptic fixation and its correlation with lens optic centration-decentration in a large series of eyes with PC-IOLs obtained postmortem. - Design - Prospective analysis of pseudophakic eyes obtained postmortem. - Participants - A total of 3493 human eyes obtained postmortem, the largest database of such specimens available to date. - Methods - Miyake-Apple posterior photographic technique. - Main outcome measures - The amount of decentration of rigid PC-IOLs and small-incision foldable PC-IOLs was analyzed, and the results were correlated with the type of fixation that had been achieved in each case. - Results - Determination of mean values revealed that capsular bag fixation was achieved in 52.05% of eyes, asymmetric bag-sulcus fixation in 34.21% of eyes, and sulcus-sulcus fixation in 13.74% of eyes. Asymmetrically fixed lenses consistently showed significant decentration. During the past 5 years (1993-98), the overall rate of in-the-bag fixation increased to 59.2%; by 1998 it had increased to 64%. Most significantly, success in achieving bag-bag fixation of foldable IOLs implanted in association with modern capsular surgery with small incisions has surged to 90% over the past 4 years. - Conclusions - The authors found a direct correlation of decentration in eyes with asymmetric fixation, and the results underscore the need for careful in-the-bag haptic placement. Although few surgeons today would dispute the goal to implanting haptics in the capsular bag, these findings show that the overall success rate over the years has, while improving, remained surprisingly low. The overall success rate of about 60% seen with all lens designs is probably as good as can be expected with classic large-incision extracapsular techniques. However, and most important and encouraging, the success rate of haptic fixation in cases with foldable lenses has improved dramatically during the past 4 years (up to the 90% range). This coincides with the present emphasis on modern capsular surgery and small-incision techniques used to insert these lenses.